"Good design" in furniture based on the perspective of selected industry members in Metro Manila - Manalo, Angelica Mara D.; Quevedo, Ma. Teresa P. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The purpose of the study was to determine how "good design" was understood and applied in the local furniture industry. The study employed an exploratory approach and utilized data gathering methods such as secondary data analysis and interview. To determine the companies that were willing to participate in the study, a purposive sampling strategy was used. The first ten (10) companies who agreed to take part in the study comprised the final selection. Each company was asked to choose an individual who would represent them in the interview, making a total of ten (10) respondents. The instrumentation for the study included a one-page questionnaire, a notebook, pen, and an iPhone. Results revealed that the respondents recognized the Philippines as a design capital based on indicators such as the existence of a large number of designers. Although majority of the respondents acknowledged the country's competitiveness in terms of design, they could not agree on the reasons why. Most of the respondents defined "good design" in terms of function or aesthetics, and mentioned that it should be aligned with worldwide trends. In general, the respondents did not have a clear awareness of a design philosophy and associated this with business practices that were outside the realm of design. They also believed that these practices contributed to the success of their design . Most of the respondents pointed out the country's diminishing resources, along with the high price of furniture, as considerations that contributed to "good design"
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Furniture design -- Philippines; Furniture industry -- Philippines